Christianity and Empire in South Manipur Hills: Senvon Encounter and the Dialogic Zo Peoples (Review) - Vumjou, Henry (Sanata Dharma University, 2024)
Christianity and Empire in South Manipur Hills: Senvon Encounter and the Dialogic Zo Peoples. Oxford, Regnum Books International (2022), by Samuel G. Ngaihte, and Reuben Paulianding. Paperback, 166pp. 5.36. Indian Edition published by ISPCK.